2020
DOI: 10.1186/s12933-020-01093-6
|View full text |Cite
|
Sign up to set email alerts
|

Long term clinical impact of successful recanalization of chronic total occlusion in patients with and without type 2 diabetes mellitus

Abstract: Background: Diabetes mellitus is one of the risk factors for coronary artery disease and frequently associated with multivessels disease and poor clinical outcomes. Long term outcome of successful revascularization of chronic total occlusions (CTO) in diabetes patients remains controversial. Methods and results: From January 2005 to December 2015, 739 patients who underwent revascularization for CTO in Taipei Veterans General Hospital were included in this study, of which 313 (42%) patients were diabetes patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…For non-DM patients, our present study reveals that successful CTO-PCI may not be associated with a better prognosis in the long term compared to CTO-MT alone, which is consistent with previous studies [ 23 , 27 ]. However, the reasons behind the phenomenon that only the DM group, instead of the non-DM group, could benefit from CTO revascularization remain unclear.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…For non-DM patients, our present study reveals that successful CTO-PCI may not be associated with a better prognosis in the long term compared to CTO-MT alone, which is consistent with previous studies [ 23 , 27 ]. However, the reasons behind the phenomenon that only the DM group, instead of the non-DM group, could benefit from CTO revascularization remain unclear.…”
Section: Discussionsupporting
confidence: 93%
“…A total of 6 studies were included to compare successful CTO-PCI versus CTO-MT for clinical outcomes in DM patients [ 18 , 23 , 24 , 26 28 ], and 3 of 6 eligible studies reported the primary endpoint MACEs [ 18 , 23 , 27 ]. As revealed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that in patients with diabetes and TVD, PCI and CABG was associated with a lower risk of all-cause death and MACCE during follow-up, which suggested the importance of revascularization for these patients. Previous studies have shown that patients with diabetes have a worse prognosis [ 16 ] and benefits more from revascularization than non-diabetic patients [ 17 ]. However, it should be pointed out that patients in the MT group may have had different conditions, including a coronary artery with simple lesions (low SYNTAX scores) in which revascularization was not required; additionally, another condition is where a coronary artery with complex lesions (high SYNTAX scores) could not have revascularization performed.…”
Section: Discussionmentioning
confidence: 99%